“Rosary of Testes”: Splenogonadal Fusion in Association with Bilateral Abdominal Testes Presenting as Polyorchidism - Pejman Shadpour; Behkam Rezaimehr (Case Reports in Urology)
Polyorchidism is a rare anomaly where early segmentation in the gonadal ridge can lead to the development of three or less commonly four testes in one individual. Just over 150 reports of this phenomenon exist in English medical literature. However, once confronted by the clinical finding of supernumerary gonads, one must remain mindful of other likely diagnoses involving nontesticular origin. We report on a male patient with bilaterally impalpable testes in whom splenogonadal fusion mimicked polyorchidism. By keeping such differential diagnoses in mind, surgeons are more liable to take the appropriate intraoperative course of action.